THE GRAMMAR OF THE UKRAINIAN LANGUAGE AS A TOOL FOR DEVELOPING THE PROFESSIONAL LANGUAGE COMPETENCE OF HIGHER EDUCATION STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
This article examines the role of Ukrainian grammar as a crucial tool for developing professional language competence among higher education students studying non-linguistic specialties. The paper highlights the historical foundations and evolution of grammatical competence research, as well as modern approaches to integrating grammar teaching within professionally oriented language education. It emphasizes the importance of mastering grammar not only as a set of rules but as a functional mechanism that ensures accuracy, logic, and stylistic appropriateness in professional communication. The study outlines specific features of teaching grammar tailored to the needs of students in various fields, focusing on the practical application of grammatical knowledge in both oral and written professional discourse. It presents a systematic methodology involving stages of familiarization with theoretical concepts, analytical and training exercises, practical application through speech production tasks, and control-correction activities aimed at minimizing grammatical errors. Such a comprehensive approach facilitates the effective acquisition and internalization of grammar, enabling students to apply grammatical structures flexibly and correctly in different communicative situations related to their future professional activities. Furthermore, the article discusses the integration of grammar with vocabulary, stylistics, and rhetoric to form a coherent and comprehensive language competence necessary for successful professional communication in diverse contexts. The proposed system of exercises and teaching methods responds to the specific language needs of non-linguistic students and aims to enhance their overall language culture, communicative effectiveness, and confidence in specialized professional environments.
Keywords: non-philological specialties; professional communication; grammatical competence; grammar; Ukrainian language for professional purposes; language education; exercise system